Understanding inner-shell excitations in molecules through spectroscopy of the 4f hole states of YbF - Popa,S; Schaller,S; Fielicke,A; Lim,J; Sartakov,BG; Tarbutt,M; Meijer,G (Physical Review X, 2024)
Molecules containing a lanthanide atom have sets of electronic states arising from excitation of an inner-shell electron. These states have received little attention, but are thought to play an important role in laser cooling of such molecules and may be a useful resource for testing fundamental physics. We study a series of inner-shell excited states in YbF using resonance-enhanced multi-photon ionisation spectroscopy. We investigate the excited states of lowest energy, 8474, 9013 and 9090 cm¹ above the ground state, all corresponding to the configuration 4f¹³6s² ²F⁄ of the Yb ion. They are metastable, since they have no electric dipole allowed transitions to the ground state. We also characterize a state at 31050 cm¯¹ that is easily excited from both the ground and metastable states, which makes it especially useful for this spectroscopic study. Finally, we study two states at 48720 cm¯¹ and 48729 cm¯¹, which are above the ionization limit and feature strong auto-ionizing resonances that prove useful for efficient detection of the molecules and for identifying the rotational quantum number of each line in the spectrum. We resolve the rotational structures of all these states and find that they can all be described by a very simple model based on Hund’s case (c). Our study provides information necessary for laser slowing and magneto-optical trapping of YbF, which is an important species for testing fundamental physics. We also consider whether the low-lying inner-shell states may themselves be useful as probes of the electron’s electric dipole moment or of varying fundamental constants, since they are long-lived states in a laser-coolable molecule featuring closely-spaced levels of opposite parity.